Preparation method of spherical cerium oxide, cerium oxide and application thereof

The preparation of spherical cerium oxide by high-temperature calcination, airflow crushing, low-temperature secondary calcination and wet ball milling solves the problem of cerium oxide agglomeration in aqueous solution, improves its dispersion and redox properties, and significantly improves the STI polishing selection ratio and wafer surface quality.

CN119160926APending Publication Date: 2024-12-20WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202310723622.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Cerium oxide is prone to agglomeration in aqueous solution, resulting in a decrease in effective abrasives in the polishing liquid, a decrease in polishing efficiency, and an increase in surface scratches, affecting the STI polishing selection ratio and wafer polishing surface quality.

Method used

Spherical cerium oxide is prepared by high-temperature calcination, airflow crushing, low-temperature secondary calcination, wet ball milling and secondary seed growth to improve its dispersion and redox properties, and enhance the polishing selection ratio and surface quality.

Benefits of technology

By improving the dispersion and redox performance of cerium oxide, the P-TEOS polishing rate and polishing selection ratio are improved, the wafer polishing damage is reduced, and the STI polishing effect is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004292013460000101
    Figure BDA0004292013460000101
  • Figure BDA0004292013460000166
    Figure BDA0004292013460000166
  • Figure BDA0004292013460000171
    Figure BDA0004292013460000171
Patent Text Reader

Abstract

The invention discloses a preparation method of spherical cerium oxide, cerium oxide and application of cerium oxide, and sphere-like cerium oxide particles are prepared through high-temperature calcination, jet milling, low-temperature secondary calcination, wet ball milling and secondary seed crystal growth. According to the preparation method, the particle size uniformity and dispersity in the cerium oxide wet ball milling process are improved, the surface smoothness of cerium oxide particles is improved through secondary seed crystal growth, and the number of edges and corners is small; meanwhile, the change of the morphology of the cerium oxide also promotes the increase of the Ce < 3 + > content on the surface of the cerium oxide, so that the oxygen vacancy and the oxidation-reduction performance of the cerium oxide are improved, and the polishing rate and the polishing selection ratio of P-TEOS are improved. According to the invention, the problems of dispersion stability of the cerium oxide abrasive in STI polishing and wafer polishing surface quality are solved, and the STI polishing selection ratio is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material preparation and semiconductor polishing, and particularly relates to a preparation method of spherical cerium oxide, cerium oxide and application thereof in the field of STI polishing. Background Art

[0002] The manufacturing of COMS chips is to integrate hundreds of millions of active devices on a silicon substrate, so as to design various circuits to obtain logic and analog functions. The electrical isolation performance between different devices is a key indicator for evaluating chip performance, so it is necessary to use insulating materials to isolate different devices. At present, shallow trench isolation (STI) is used in the industry to establish isolation areas between active devices. The process of shallow trench isolation is to first grow an isolation silicon dioxide layer and silicon nitride on the silicon substrate, then perform STI groove etching and STI silicon oxide filling, and then use chemical mechanical polishing (CMP) technology to polish the STI silicon dioxide and stop on silicon nitride, and finally use hot phosphoric acid to remove the silicon nitride.

[0003] At present, the CMP polishing liquid for shallow trench isolation with a process node of 28nm and below is mainly cerium oxide (CeO2). The reason is that cerium oxide polishing liquid not only has a higher silicon oxide polishing rate, but also has a higher polishing selectivity (silicon oxide relative to silicon nitride), which is difficult to achieve with traditional silicon oxide (SiO2) and aluminum oxide (Al2O3) polishing liquids. Therefore, cerium oxide is irreplaceable in STI polishing. The high polishing rate and selectivity of cerium oxide are attributed to its unique chemical polishing characteristics: the surface of cerium oxide has abundant oxygen vacancies, which can form strong chemical bonds with oxygen atoms in the silicon oxide of the polishing layer, thereby producing a higher polishing rate, while there are no oxygen atoms in silicon nitride, so it is weakly bonded with cerium oxide and has a low polishing rate.

[0004] The preparation method of industrial cerium oxide is mainly to use cerium carbonate as a precursor for calcination and grinding. For example, CN106927495A and KR1020070043156 disperse the cerium oxide obtained by calcining cerium carbonate at high temperature in water, and the obtained slurry can significantly reduce its particle size through wet ball milling, showing good flattening polishing efficiency in STI polishing applications. JP4983603B2 pulverizes the cerium oxide obtained by calcining cerium carbonate at high temperature by air flow to obtain micron to submicron cerium oxide, disperse it in an anionic surfactant aqueous solution, centrifuge and filter it, remove large particles, and obtain nano-scale cerium oxide that can be used for STI polishing.

[0005] When cerium oxide is used to prepare polishing liquid in aqueous solution, it is very easy to agglomerate, condense into larger particles and quickly settle in a short time, resulting in a reduction in effective abrasive in the polishing liquid and a decrease in polishing efficiency. At the same time, it will increase surface scratches, resulting in an increase in surface defects in the silicon oxide layer after polishing. In addition, compared with traditional silicon oxide abrasives, cerium oxide abrasives have significant advantages in improving the STI polishing selectivity, but currently it is generally lower than 30 and needs to be further improved. The particle size, dispersibility, morphology and surface properties of cerium oxide have an important influence on the polishing selectivity in the STI process. At present, the improvement of STI polishing selectivity and wafer polishing surface quality is still a key issue. Summary of the invention

[0006] In view of the above problems, the present invention innovatively proposes a method for preparing spherical cerium oxide. The cerium oxide prepared by the method is used as a polishing abrasive to improve the STI polishing selectivity of the cerium oxide abrasive and the polishing surface quality of the wafer.

[0007] Another object of the present invention is to provide spherical cerium oxide prepared by the preparation method.

[0008] Another object of the present invention is to provide application of spherical cerium oxide prepared by the preparation method in the field of STI polishing.

[0009] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:

[0010] A method for preparing spherical cerium oxide comprises the following steps:

[0011] 1) Calcination: The cerium salt is placed in a crucible and calcined once to obtain cerium oxide, which is then crushed and calcined twice;

[0012] 2) Dispersion: adding the cerium oxide obtained by secondary calcination into an aqueous solution containing an anionic surfactant, adjusting the pH of the cerium oxide dispersion to alkaline with a pH adjuster, and stirring and dispersing;

[0013] 3) Wet grinding: using a ball mill to wet grind the cerium oxide dispersion in step 2) to obtain a cerium oxide slurry of 50-1000 nm;

[0014] 4) Secondary growth: The nano-sized cerium oxide slurry of step 3) is washed and dried, dispersed in water as seed crystals, cerium salt and alkali are added, mixed and stirred, and the purple slurry is transferred to a reactor for secondary growth to obtain spherical cerium oxide.

[0015] In a specific embodiment, the cerium salt in step 1) is cerium carbonate, and preferably the particle size of cerium carbonate is 0.1-50 μm;

[0016] Preferably, the primary calcination temperature is 700-900°C, preferably 700-800°C, and the calcination time is 2-8h, preferably 4-6h;

[0017] Preferably, the cerium oxide is dry-ground by airflow grinding, and the particle size of the cerium oxide after airflow grinding is 0.1-30 μm and the specific surface area is 5-13 m 2 / g, preferably 7-10m 2 / g;

[0018] Preferably, the secondary calcination temperature is 400-650°C, preferably 550-650°C, and the calcination time is 2-8h, preferably 4-6h.

[0019] In a specific embodiment, the solid content of cerium oxide in the cerium oxide dispersion in step 2) is 10-50 wt %;

[0020] Preferably, the anionic surfactant is selected from any one of triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, and polycarboxylic acid type polymer dispersants; More preferably, the polycarboxylic acid type polymer dispersant is a copolymer of a carboxylic acid monomer with an unsaturated double bond, a copolymer of a carboxylic acid monomer with an unsaturated double bond and a monomer with other unsaturated double bonds, and an ammonium salt or an amine salt thereof, and the carboxylic acid monomer with an unsaturated double bond is selected from any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, polymaleic acid, polyfumaric acid, and polyitaconic acid;

[0021] Preferably, the anionic surfactant is selected from at least any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid or ammonium polymethacrylate;

[0022] Preferably, the molecular weight of the anionic surfactant is 2000-10000, preferably 2000-3000; the amount of the anionic surfactant added is 1 / 1000-1 / 50 of the mass of cerium oxide, preferably 1 / 1000-1 / 100.

[0023] In a specific embodiment, the pH adjuster in step 2) is selected from at least any one of KOH, NaOH, K2CO3, (NH4)2CO3, NH4HCO3, ammonia water and tetramethylammonium hydroxide;

[0024] Preferably, the pH of the dispersion is adjusted to 8-11, preferably 8-9;

[0025] Preferably, the stirring time for stirring and dispersing is 1-8 h, preferably 1-4 h.

[0026] In a specific embodiment, the ball mill speed in step 3) is 1000-3000 rpm, preferably 1500-2200 rpm; the zirconium bead size is 0.1-0.5 mm, preferably 0.1-0.3 mm; and the grinding time is 20-60 min, preferably 20-40 min.

[0027] In a specific embodiment, the nano-scale cerium oxide slurry in step 4) is washed with water, the drying temperature is 50-100° C., and the drying time is 10-15 h; preferably, the seed crystals are dispersed in water, and the amount of seed crystals added is 100-400 g.

[0028] In a specific embodiment, the cerium salt in step 4) is any one of cerium nitrate, cerium chloride, and cerium oxalate, preferably Ce(NO3)3·6H2O, and the concentration of the cerium salt solution is 15-30wt%, preferably 22-27wt%; the base is any one of KOH, NaOH, and ammonia water, preferably KOH, and the concentration of the KOH solution is 15-35wt%, preferably 19-25wt%; preferably, the reaction temperature of the secondary growth is 100-180°C, preferably 130-160°C; the reaction time of the secondary growth is 5-15h, preferably 9-13h.

[0029] On the other hand, the spherical cerium oxide prepared by the above-mentioned preparation method preferably has a particle size distribution dispersion of 1-2 and a surface Ce 3+ The content is 20-40%; more preferably, the STI polishing selectivity is not less than 30.

[0030] On the other hand, the spherical cerium oxide prepared by the aforementioned preparation method or the application of the spherical cerium oxide in the field of STI polishing, preferably, the prepared spherical cerium oxide is added to an aqueous solution containing an anionic surfactant, the pH of the cerium oxide dispersion is adjusted to alkaline to form a cerium oxide slurry, and when in use, the cerium oxide slurry is diluted with deionized water before polishing.

[0031] In a specific embodiment, the anionic surfactant is selected from any one of triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, and polycarboxylic acid type polymer dispersants; preferably, the polycarboxylic acid type polymer dispersant is a copolymer of a carboxylic acid monomer with an unsaturated double bond, a copolymer of a carboxylic acid monomer with an unsaturated double bond and a monomer with other unsaturated double bonds, and an ammonium salt or amine salt thereof, and the carboxylic acid monomer with an unsaturated double bond is selected from any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, polymaleic acid, polyfumaric acid, and polyitaconic acid; more preferably, the molecular weight of the anionic surfactant is 2000-10000, preferably 2000-3000; the content of the anionic surfactant in the cerium oxide slurry before dilution is 0.1-1wt% of the total mass of the cerium oxide slurry as the polishing liquid, preferably 0.3-0.6wt%;

[0032] Preferably, the pH regulator is at least one of KOH, NaOH, K2CO3, (NH4)2CO3, NH4HCO3, ammonia water and tetramethylammonium hydroxide; the pH is adjusted to 8-11, preferably 8-9;

[0033] Preferably, the solid content of cerium oxide in the cerium oxide slurry before dilution is 0.1-1.0 wt %, preferably 0.1-0.5 wt %.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The preparation method of the present invention prepares spherical cerium oxide particles through high-temperature calcination, air flow crushing, low-temperature secondary calcination, wet ball milling and secondary seed growth, improves the dispersibility of cerium oxide, reduces wafer polishing damage, and improves Ce 3+ content and redox properties, thereby achieving an improvement in the polishing rate and polishing selectivity of P-TEOS. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The XRD spectra of cerium oxide obtained by calcining at 700° C. in Examples 2 and 3 of the present invention and Comparative Example 5 are shown.

[0037] Figure 2 The SEM / TEM spectra of cerium oxide obtained after different process treatments in Examples 2 and 3 of the present invention and Comparative Example 5, wherein: (a) SEM of cerium oxide obtained by calcination at 700°C; (b) SEM of cerium oxide obtained by air flow crushing; (c) SEM of cerium oxide obtained by secondary calcination at 600°C; (d) TEM of cerium oxide obtained by filtration after wet crushing.

[0038] Figure 3TEM spectra of cerium oxide obtained under different experimental conditions in the examples and comparative examples of the present invention, wherein (a) Example 2; (b) Example 3; (c) Comparative Example 1; (d) Comparative Example 2; (e) Comparative Example 3; and (f) Comparative Example 4. DETAILED DESCRIPTION

[0039] In order to better understand the technical solution of the present invention, the preparation method of the present invention is further explained below through more specific examples, but it does not constitute any limitation.

[0040] A method for preparing spherical cerium oxide comprises the following steps:

[0041] 1) Calcination of cerium oxide: cerium carbonate is placed in an alumina crucible and calcined at high temperature to obtain cerium oxide; the cerium oxide is dry-pulverized by air flow milling, and the obtained cerium oxide is secondary calcined at low temperature.

[0042] 2) Cerium oxide dispersion: The cerium oxide obtained by secondary calcination is added to a certain aqueous solution containing an anionic surfactant, the pH of the cerium oxide dispersion is adjusted to alkaline, and stirred for a certain period of time.

[0043] 3) Wet grinding of cerium oxide: Use a ball mill to wet grind the cerium oxide dispersion. By adjusting the rotation speed, zirconium beads and grinding time, nano-scale cerium oxide slurry is obtained. The obtained cerium oxide slurry is passed through a membrane filter with a pore size of 1 μm to remove coarse particles in the slurry.

[0044] 4) Secondary growth of cerium oxide: The nano-scale cerium oxide slurry is washed and dried, the obtained seed crystals are dispersed in water, stirred, and a certain concentration of Ce(NO3)3·6H2O aqueous solution and a certain concentration of KOH aqueous solution are added, mixed and stirred; then the purple slurry is transferred to a flask and reacted at a certain temperature for a certain time for secondary growth to obtain spherical cerium oxide.

[0045] Wherein, the particle size of cerium carbonate in step 1) is 0.1-50 μm, for example, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc., the high temperature calcination temperature is 700-900 ° C, for example, 720 ° C, 750 ° C, 780 ° C, 800 ° C, 815 ° C, 850 ° C, 875 ° C, 900 ° C, etc., preferably 700-800 ° C, and the calcination time is 2-8 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, etc., preferably 4-6 h.

[0046] The pulverization in step 1) can be air flow pulverization or other dry pulverization, preferably air flow pulverization. The particle size of cerium oxide after pulverization is 0.1-30 μm, such as 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc., and the specific surface area is 5-13 m 2 / g, for example 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, etc., preferably 7-10m 2 / g. The low-temperature calcination temperature for the low-temperature secondary calcination is 400-650°C, such as 420°C, 450°C, 480°C, 500°C, 515°C, 550°C, 575°C, 600°C, 625°C, 650°C, etc., preferably 550-650°C, and the calcination time is 2-8h, such as 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc., preferably 4-6h.

[0047] The cerium oxide in step 2) is added to an aqueous solution containing an anionic surfactant, and the solid content of the cerium oxide is 10-50wt%, for example, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc. The anionic surfactant is triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, polycarboxylic acid type polymer dispersant; the polycarboxylic acid type polymer dispersant includes copolymers of carboxylic acid monomers having unsaturated double bonds such as polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, polymaleic acid, polyfumaric acid, polyitaconic acid, etc., and carboxylic acid monomers having unsaturated double bonds and monomers having other unsaturated double bonds. copolymers of cerium oxide, and their ammonium salts or amine salts; preferably, the anionic surfactant is at least any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid or ammonium polymethacrylate; the molecular weight of the anionic surfactant is 2000-10000, such as 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, preferably 2000-3000; the content of the anionic surfactant is 1 / 1000-1 / 50 of the mass of cerium oxide, such as 1 / 900, 1 / 800, 1 / 700, 1 / 600, 1 / 500, 1 / 400, 1 / 300, 1 / 200, 1 / 100, etc., preferably 1 / 1000-1 / 100.

[0048] In step 2), the pH adjuster is at least any one of KOH, NaOH, K2CO3, (NH4)2CO3, NH4HCO3, ammonia water and tetramethylammonium hydroxide; the pH is adjusted to 8-11, for example, 8.5, 9, 9.5, 10, 10.5, 11, etc., preferably 8-9; the stirring time is 1-8h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc., preferably 1-4h.

[0049] In step 3), wet ball milling is used for wet pulverization, the ball mill speed is 1000-3000rpm, such as 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, etc., preferably 1500-2200rpm; the zirconium bead size is 0.1-0.5mm, such as 0.2mm, 0.3mm, 0.4mm, etc., preferably 0.1-0.3mm; the ball milling time is 20-60min, such as 20min, 30min, 40min, 50min, 60min, etc., preferably 20-40min. Nano-scale cerium oxide slurry is obtained by wet ball milling, for example, ball milling to 50-1000nm, preferably 50-500nm.

[0050] In step 4), the concentration of Ce(NO3)3·6H2O is 15-30wt%, preferably 22-27wt%; the concentration of KOH is 15-35wt%, preferably 19-25wt%; the mass ratio of the two is 1:1-1:3; the reaction temperature of the secondary growth is 100-180℃, for example, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, etc., preferably 130-160℃; the reaction time of the secondary growth is 5-15h, for example, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, etc., preferably 9-13h.

[0051] The spherical cerium oxide prepared by the present invention is cooled to room temperature, added into a certain aqueous solution containing anionic surfactant, and the pH of the cerium oxide dispersion is adjusted to alkaline to obtain a polishing liquid slurry with cerium oxide as an abrasive; the obtained cerium oxide slurry is diluted with deionized water before use and then polishing can be performed.

[0052] Wherein, the anionic surfactant is triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, and polycarboxylic acid type polymer dispersant; the polycarboxylic acid type polymer dispersant includes copolymers of carboxylic acid monomers with unsaturated double bonds such as polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, polymaleic acid, polyfumaric acid, and polyitaconic acid, copolymers of carboxylic acid monomers with unsaturated double bonds and monomers with other unsaturated double bonds, and their ammonium salts or amine salts; preferably, the anionic surfactant is at least any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, or ammonium polymethacrylate; the molecular weight of the anionic surfactant is 2000-10000, preferably 2000-3000; the anionic surfactant may be the same or different from that in step 2), preferably the same as that in step 2). The content of anionic surfactant is 0.1-1wt% of the total mass of cerium oxide slurry as polishing liquid, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, etc., preferably 0.3-0.6wt%.

[0053] The pH regulator is at least one of KOH, NaOH, K2CO3, (NH4)2CO3, NH4HCO3, ammonia and tetramethylammonium hydroxide; the pH is adjusted to 8-11, preferably 8-9. The solid content of cerium oxide in the cerium oxide slurry as the polishing liquid is 0.1-1.0wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, etc., preferably 0.1-0.5wt%.

[0054] The main raw materials used in the following examples and comparative examples are as follows:

[0055]

[0056] Detection method:

[0057] The particle size was measured using a laser diffraction particle size analyzer, with the light shielding ratio set to 2.2 and the light absorbance set to 1.3. The particle size was measured after ultrasound. The results are shown in Table 1, and no agglomeration was observed. (D90-D10) / D50 represents the dispersion of the particle size distribution.

[0058] XRD (X-ray diffraction) was used to detect the sample phase; SEM (transmission electron microscopy) was used to detect the micron-level cerium oxide morphology and particle size; TEM (transmission electron microscopy) was used to detect the nano-level cerium oxide morphology and particle size. XPS (X-ray photoelectron spectroscopy) was used to detect the Ce on the surface of cerium oxide. 3+ content.

[0059] P-TEOS polishing rate evaluation:

[0060] A P-TEOS wafer with a diameter of 2 inches and a film thickness of 2 μm was used for insulating film CMP evaluation. The wafer was placed on the holder of the adsorption pad for mounting the substrate in the polishing device (Shenyang Kejing UNIPOL-1000S), and a porous polyurethane resin polishing pad (k-groove groove, manufactured by Rodel, model-IC1000) was attached to the polishing disc with a diameter of 300 mm. The holder was placed on the polishing pad so that the insulating film of the wafer faced down, and the wafer pressure was set to 3 psi. At the same time, cerium oxide polishing liquid was dripped on the polishing disc at a flow rate of 100 mL / min, and the polishing disc and wafer were rotated at 60 rpm and 70 rpm, respectively, to polish the above P-TEOS film for 1 minute. The polished wafer was thoroughly cleaned with pure water and dried, and then the residual film thickness of the SiO2 film at 10 points on the wafer surface was measured using an optical interference film thickness device. The polishing rate was calculated based on the reduction in film thickness compared to before polishing. The results are shown in Table 1.

[0061] Evaluation of polishing damage:

[0062] The polished P-TEOS wafer was immersed in a 0.5% hydrofluoric acid solution for 1 minute to remove the residual cerium oxide particles, and then thoroughly rinsed with pure water. Then, the P-TEOS surface was inspected for the number of defects using a defect inspection device (KLAT Teco, USA). The results are shown in Table 1.

[0063] Evaluation of polishing selectivity:

[0064] The silicon nitride wafer obtained by LPCVD (low pressure chemical vapor deposition) was polished in the same polishing manner as the above-mentioned P-TEOS wafer, and the thickness change before and after polishing was measured using the same system. The results are shown in Table 1. The ratio of the P-TEOS polishing rate to the silicon nitride polishing rate is the polishing selectivity.

[0065] The main process conditions of each embodiment and comparative example are as follows:

[0066] Comparative Example 1

[0067] 2 kg of cerium carbonate was placed in an alumina crucible and calcined at 700 °C for 4 h in a muffle furnace. The obtained cerium oxide was calcined again at 600 °C for 4 h for secondary calcination. The specific surface area of ​​the cerium oxide was 3.5 m 2 / g. 200g of cerium oxide obtained by secondary calcination was added to an aqueous solution of ammonium polyacrylate, wherein the solid content of cerium oxide was 10wt% and the content of ammonium polyacrylate was 1 / 100 of the mass of cerium oxide. The pH of the cerium oxide dispersion was adjusted to 9 using KOH and stirred for 1h. The cerium oxide dispersion was wet-ground using a ball mill, wherein the rotation speed was 2000rmp, the zirconium bead size was 0.2mm, and the grinding time was 30min. Finally, the obtained cerium oxide slurry was passed through a membrane filter with a pore size of 1μm to remove the coarse particles in the slurry, and a cerium oxide slurry with a particle size distribution of about 100-473nm and an average particle size of 161nm was obtained. The specific surface area measured by BET was 34.8m 2 / g, TEM shows that the particle size is 6-82nm, such as Figure 3 c. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 27%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 9, and the polishing rate of silicon nitride is Comparative Example 2

[0068] 2 kg of cerium carbonate was placed in an alumina crucible and calcined at 700 °C for 8 h in a muffle furnace to obtain 1 kg of yellow-white powder. The specific surface area of ​​the powder was 3.1 m 2 / g. 200g of cerium oxide obtained by secondary calcination was added to an aqueous solution of ammonium polyacrylate, wherein the solid content of cerium oxide was 10wt% and the content of ammonium polyacrylate was 1 / 100 of the mass of cerium oxide. The pH of the cerium oxide dispersion was adjusted to 9 using KOH and stirred for 1h. The cerium oxide dispersion was wet-ground using a ball mill, wherein the rotation speed was 2000rmp, the zirconium bead size was 0.2mm, and the grinding time was 30min. Finally, the obtained cerium oxide slurry was passed through a membrane filter with a pore size of 1μm to remove the coarse particles in the slurry, and a cerium oxide slurry with a particle size distribution of about 103-475nm and an average particle size of 163nm was obtained. The specific surface area measured by BET was 35.1m 2 / g, TEM shows that the particle size is 6-98nm, such as Figure 3 d. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 24%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 11, and the polishing rate of silicon nitride is Comparative Example 3

[0069] 2 kg of cerium carbonate was placed in an alumina crucible and calcined at 800 °C for 8 h in a muffle furnace to obtain 1 kg of yellow-white powder. The BET specific surface area was 2.8 m 2 / g. 200g of cerium oxide obtained by secondary calcination was added to an aqueous solution of ammonium polyacrylate, wherein the solid content of cerium oxide was 10wt% and the content of ammonium polyacrylate was 1 / 100 of the mass of cerium oxide. The pH of the cerium oxide dispersion was adjusted to 9 using KOH and stirred for 1h. The cerium oxide dispersion was wet-ground using a ball mill, wherein the rotation speed was 2000rmp, the zirconium bead size was 0.2mm, and the grinding time was 30min. Finally, the obtained cerium oxide slurry was passed through a membrane filter with a pore size of 1μm to remove the coarse particles in the slurry, and a cerium oxide slurry with a particle size distribution of about 91-494nm and an average particle size of 162nm was obtained. The specific surface area measured by BET was 33.1m 2 / g, TEM shows that the particle size is 4-113nm, such as Figure 3 e. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 23%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 13, and the polishing rate of silicon nitride is Comparative Example 4

[0070] 2 kg of cerium carbonate was placed in an alumina crucible and calcined at 900 °C for 8 h in a muffle furnace to obtain 1 kg of yellow-white powder. The BET specific surface area was 2.5 m 2 / g. 200g of cerium oxide obtained by secondary calcination was added to an aqueous solution of ammonium polyacrylate, wherein the solid content of cerium oxide was 10wt% and the content of ammonium polyacrylate was 1 / 100 of the mass of cerium oxide. The pH of the cerium oxide dispersion was adjusted to 9 using KOH and stirred for 1h. The cerium oxide dispersion was wet-ground using a ball mill, wherein the rotation speed was 2000rmp, the zirconium bead size was 0.2mm, and the grinding time was 30min. Finally, the obtained cerium oxide slurry was passed through a membrane filter with a pore size of 1μm to remove the coarse particles in the slurry, and a cerium oxide slurry with a particle size distribution of about 80-522nm and an average particle size of 164nm was obtained. The specific surface area measured by BET was 32.8m 2 / g, TEM shows that the particle size is 9-114nm, such as Figure 3 f. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 21%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 16, and the polishing rate of silicon nitride is Comparative Example 5

[0071] 2 kg of cerium carbonate was placed in an alumina crucible and calcined at 700 °C for 5 h in a muffle furnace to obtain 1 kg of yellow-white powder. XRD showed that its phase was cubic fluorite phase cerium oxide, such as Figure 1 ; BET measured its specific surface area to be 4.3m2 / g, SEM shows that the particle size is 50-200μm, such as Figure 2 a. The cerium oxide was dry-ground by air flow milling, and its specific surface area was 9.0 m 2 / g, SEM shows that the particle size is 0.5-20μm, such as Figure 2 b. The obtained cerium oxide was calcined again at 600°C for 6 hours for secondary calcination. The specific surface area measured by BET was 8.5 m 2 / g, SEM shows that the particle size is 0.6-20μm, such as Figure 2 c. 200 g of cerium oxide obtained by secondary calcination was added to an aqueous solution of ammonium polyacrylate, wherein the solid content of cerium oxide was 10 wt % and the content of ammonium polyacrylate was 1 / 100 of the mass of cerium oxide. The pH of the cerium oxide dispersion was adjusted to 9 using KOH and stirred for 1 hour. The cerium oxide dispersion was wet-milled using a ball mill, wherein the rotation speed was 2000 rpm, the zirconium bead size was 0.2 mm, and the grinding time was 30 minutes. Finally, the obtained cerium oxide slurry was passed through a membrane filter with a pore size of 1 μm to remove the coarse particles in the slurry, and a cerium oxide slurry with a particle size distribution of about 100-350 nm and an average particle size of 160 nm was obtained. The specific surface area measured by BET was 32.2 m 2 / g, TEM shows that the particle size is 8-60nm. Figure 2 d. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 29%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 4, and the polishing rate of silicon nitride is

[0072] Example 1

[0073] The primary calcination temperature in Comparative Example 5 was changed to 900°C, and the stirring time of the cerium oxide dispersion process was adjusted to 3h. The other preparation methods were the same. The specific surface area of ​​the cerium oxide obtained by the primary calcination was 3.5m 2 / g, SEM measured the particle size to be 72-210μm. The specific surface area of ​​cerium oxide after air flow pulverization is 6.7m 2 / g, SEM measured the particle size to be 0.9-29μm. After secondary calcination, the specific surface area was 7.7m 2 / g, SEM measured particle size of 0.6-25μm. The particle size distribution of cerium oxide slurry obtained by wet grinding and filtration was about 128-459nm, the average particle size was 187nm, and the specific surface area measured by BET was 29.3m 2 / g. The filtered cerium oxide slurry was centrifuged and washed, and dried at 80°C for 12 hours to obtain cerium oxide powder. Weigh 200g of the dried cerium oxide as seeds and disperse them in 1000g of water, stir for 30 minutes, add 500g of Ce(NO3)3·6H2O aqueous solution (25.2wt%) and 500g of KOH aqueous solution (21.2wt%), mix and stir for 30 minutes. Then transfer the purple slurry to a 5L flask and react at 150°C for 10 hours for secondary growth. After the reactant is cooled to room temperature, 500g of ammonium polyacrylate aqueous solution (0.5wt%) is added, and the pH of the slurry is adjusted to 9 using KOH to obtain a cerium oxide slurry with a particle size distribution of about 133-420nm and an average particle size of 187nm. The specific surface area measured by BET is 19.3m 2 / g, and the particle size measured by TEM was 18-90nm. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 30%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 4, and the polishing rate of silicon nitride is

[0074] Example 2

[0075] A cerium oxide slurry with a particle size distribution of about 100-350 nm and an average particle size of 160 nm was prepared in the same manner as described in Comparative Example 5, washed by centrifugation, and dried at 80°C for 10 hours to obtain a cerium oxide powder. Weigh 200 g of the dried cerium oxide as seeds and disperse them in 1000 g of water, stir for 40 minutes, add 500 g of Ce(NO3)3·6H2O aqueous solution (25.2 wt%) and 500 g of KOH aqueous solution (21.2 wt%), mix and stir for 30 minutes. Then transfer the purple slurry to a 5L flask and react at 150°C for 10 hours for secondary growth. After the reactant is cooled to room temperature, 500 g of ammonium polyacrylate aqueous solution (0.5 wt%) is added, and the pH of the slurry is adjusted to 9 using KOH to obtain a cerium oxide slurry with a particle size distribution of about 110-380 nm and an average particle size of 170 nm. The specific surface area measured by BET is 28.1 m 2 / g, TEM shows that the particle size is 12-71nm, such as Figure 3 a. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 34%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 1, and the polishing rate of silicon nitride is

[0076] Example 3

[0077] A cerium oxide slurry with a particle size distribution of about 100-350 nm and an average particle size of 160 nm was prepared in the same manner as described in Comparative Example 5, centrifuged and washed, and dried at 60°C for 12 hours to obtain a cerium oxide powder. Weigh 200 g of the dried cerium oxide as seeds and disperse them in 1000 g of water, stir for 40 minutes, add 500 g of Ce(NO3)3·6H2O aqueous solution (40.2 wt%) and 500 g of KOH aqueous solution (33.9 wt%), mix and stir for 30 minutes. Then transfer the purple slurry to a 5L flask and react at 150°C for 11 hours for secondary growth. After the reactant is cooled to room temperature, 500 g of ammonium polyacrylate aqueous solution (0.5 wt%) is added, and the pH of the slurry is adjusted to 9 using KOH to obtain a cerium oxide slurry with a particle size distribution of about 115-403 nm and an average particle size of 179 nm. The specific surface area measured by BET is 22.1 m 2 / g, TEM shows that the particle size is 15-72nm, such as Figure 3 b. The obtained cerium oxide slurry was diluted to 0.25wt% for polishing test, as shown in Table 1, Ce 3+ The content is 32%, and the P-TEOS polishing rate is The number of polishing damages on a single wafer is 2, and the polishing rate of silicon nitride is

[0078] Table 1 Product parameters in each embodiment and comparative example

[0079]

[0080]

[0081] As can be seen from the table above, the embodiment of the present invention uses air flow pulverization and secondary seed growth on the ball-milled cerium oxide slurry, and the cerium oxide particles are spherical, with improved surface smoothness and fewer edges and corners, which significantly reduces the number of wafer polishing damage. At the same time, the change in the morphology of cerium oxide also promotes the surface Ce of cerium oxide. 3+ The increase in the content increases the oxygen vacancies and redox properties of cerium oxide, thereby improving the P-TEOS polishing rate and STI polishing selectivity.

[0082] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing spherical cerium oxide, characterized in that: The following steps are included: 1) Calcination: The cerium salt is placed in a crucible and calcined once to obtain cerium oxide, which is then crushed and calcined twice; 2) Dispersion: adding the cerium oxide obtained by secondary calcination into an aqueous solution containing an anionic surfactant, adjusting the pH of the cerium oxide dispersion to alkaline with a pH adjuster, and stirring and dispersing; 3) Wet grinding: using a ball mill to wet grind the cerium oxide dispersion in step 2) to obtain a cerium oxide slurry of 50-1000 nm; 4) Secondary growth: The nano-sized cerium oxide slurry of step 3) is washed and dried, dispersed in water as seed crystals, cerium salt and alkali are added, mixed and stirred, and the purple slurry is transferred to a reactor for secondary growth to obtain spherical cerium oxide.

2. The preparation method according to claim 1, characterized in that: In step 1), the cerium salt is cerium carbonate, and preferably the particle size of the cerium carbonate is 0.1-50 μm; Preferably, the primary calcination temperature is 700-900°C, preferably 700-800°C, and the calcination time is 2-8h, preferably 4-6h; Preferably, the cerium oxide is dry-ground by airflow grinding, and the particle size of the cerium oxide after airflow grinding is 0.1-30 μm and the specific surface area is 5-13 m 2 / g, preferably 7-10m 2 / g; Preferably, the secondary calcination temperature is 400-650°C, preferably 550-650°C, and the calcination time is 2-8h, preferably 4-6h.

3. The preparation method according to claim 1, characterized in that: The solid content of cerium oxide in the cerium oxide dispersion in step 2) is 10-50wt%; Preferably, the anionic surfactant is selected from any one of triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, and polycarboxylic acid type polymer dispersants; More preferably, the polycarboxylic acid type polymer dispersant is a copolymer of a carboxylic acid monomer with an unsaturated double bond, a copolymer of a carboxylic acid monomer with an unsaturated double bond and a monomer with other unsaturated double bonds, and an ammonium salt or an amine salt thereof, and the carboxylic acid monomer with an unsaturated double bond is selected from any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, polymaleic acid, polyfumaric acid, and polyitaconic acid; Preferably, the anionic surfactant is selected from at least any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid or ammonium polymethacrylate; Preferably, the molecular weight of the anionic surfactant is 2000-10000, preferably 2000-3000; the amount of the anionic surfactant added is 1 / 1000-1 / 50 of the mass of cerium oxide, preferably 1 / 1000-1 / 100.

4. The preparation method according to claim 1 or 3, characterized in that: The pH regulator in step 2) is selected from at least one of KOH, NaOH, K2CO3, (NH4)2CO3, NH4HCO3, ammonia water and tetramethylammonium hydroxide; Preferably, the pH of the dispersion is adjusted to 8-11, preferably 8-9; Preferably, the stirring time for stirring and dispersing is 1-8 h, preferably 1-4 h.

5. The preparation method according to claim 1, characterized in that: In step 3), the ball mill has a rotation speed of 1000-3000 rpm, preferably 1500-2200 rpm; the zirconium bead size is 0.1-0.5 mm, preferably 0.1-0.3 mm; and the grinding time is 20-60 min, preferably 20-40 min.

6. The preparation method according to claim 1, characterized in that: In step 4), the nano-scale cerium oxide slurry is washed with water at a drying temperature of 50-100° C. for a drying time of 10-15 h. Preferably, the seed crystals are dispersed in water, and the amount of seed crystals added is 100-400 g.

7. The preparation method according to claim 1 or 6, characterized in that: In step 4), the cerium salt is any one of cerium nitrate, cerium chloride, and cerium oxalate, preferably Ce(NO3)3·6H2O, and the concentration of the cerium salt solution is 15-30wt%, preferably 22-27wt%; the base is any one of KOH, NaOH, and ammonia water, preferably KOH, and the concentration of the KOH solution is 15-35wt%, preferably 19-25wt%; preferably, the reaction temperature of the secondary growth is 100-180°C, preferably 130-160°C; the reaction time of the secondary growth is 5-15h, preferably 9-13h.

8. The spherical cerium oxide prepared by the preparation method according to any one of claims 1 to 7, preferably, the particle size distribution dispersion of the spherical cerium oxide is 1-2, and the surface Ce 3+ The content is 20-40%; more preferably, the STI polishing selectivity is not less than 30.

9. Application of the spherical cerium oxide prepared by the preparation method according to any one of claims 1 to 7 or the spherical cerium oxide according to claim 8 in the field of STI polishing. Preferably, the prepared spherical cerium oxide is added to an aqueous solution containing an anionic surfactant, and the pH of the cerium oxide dispersion is adjusted to alkaline to form a cerium oxide slurry. When in use, the cerium oxide slurry is diluted with deionized water before polishing.

10. The use of spherical cerium oxide in the field of STI polishing according to claim 9, characterized in that: The anionic surfactant is selected from any one of triethanolamine dodecyl sulfate, ammonium dodecyl sulfate, triethanolamine polyoxyethylene alkyl ether sulfate, and polycarboxylic acid type polymer dispersant; preferably, the polycarboxylic acid type polymer dispersant is a copolymer of a carboxylic acid monomer with an unsaturated double bond, a copolymer of a carboxylic acid monomer with an unsaturated double bond and a monomer with other unsaturated double bonds, and an ammonium salt or amine salt thereof, and the carboxylic acid monomer with an unsaturated double bond is selected from any one of polyacrylic acid, ammonium polyacrylate, polymethacrylic acid, ammonium polymethacrylate, polymaleic acid, polyfumaric acid, and polyitaconic acid; more preferably, the molecular weight of the anionic surfactant is 2000-10000, preferably 2000-3000; the content of the anionic surfactant in the cerium oxide slurry before dilution is 0.1-1wt% of the total mass of the cerium oxide slurry as the polishing liquid, preferably 0.3-0.6wt%; Preferably, the pH regulator is at least one of KOH, NaOH, K2CO3, (NH4)2CO3, NH4HCO3, ammonia water and tetramethylammonium hydroxide; the pH is adjusted to 8-11, preferably 8-9; Preferably, the solid content of cerium oxide in the cerium oxide slurry before dilution is 0.1-1.0 wt %, preferably 0.1-0.5 wt %.

Citation Information

Patent Citations

  • Preparation method and CMP application of cerium oxide

    CN106927495A

  • Cerium oxide slurry, cerium oxide polishing solution, and method for polishing substrates using these.

    JP4983603B2

  • System for servicing phone number change guide andmethod thereof

    KR1020070043156A

Cited By

  • Monodisperse spherical cerium dioxide as well as preparation method and application thereof

    CN121020633A